The application of rock mass classification principles to coal mine design - Whittles, David N. (2000)
This thesis aims to develop a rock mass classification system for UK Coal Measure strata such that the output from the classification system may provide a means by which the strength and stiffness properties of Coal Measure strata encountered within UK coal mines may be predicted.